Outcomes of psychological therapies for prisoners with mental health problems: a systematic review and meta-analysis - Yoon, I; Slade, K; Fazel, S (American Psychological Association, 2017)
Objective Prisoners worldwide have substantial mental health needs, but the efficacy of psychological therapy in prisons is unknown. We aimed to systematically review psychological therapies with mental health outcomes in prisoners and qualitatively summarise difficulties in conducting randomized clinical trials (RCTs). Methods Prisoners worldwide have substantial mental health needs, but the efficacy of psychological therapy in prisons is unknown. We aimed to systematically review psychological therapies with mental health outcomes in prisoners and qualitatively summarise difficulties in conducting randomized clinical trials (RCTs). Results In 37 identified studies, psychological therapies showed a medium effect size (0.50, 95% CI [0.34, 0.66]) with high levels of heterogeneity with the most evidence for CBT and mindfulness-based trials. Studies that used no treatment (0.77, 95% CI [0.50, 1.03]) or waitlist controls (0.71, 95% CI [0.43, 1.00]) had larger effect sizes than those that had treatment-as-usual or other psychological therapies as controls (0.21, 95% CI [0.01, 0.41]). Effects were not sustained on follow-up at 3 and 6 months. No differences were found between group and individual therapy, or different treatment types. The use of a fidelity measure was associated with lower effect sizes. Qualitative analysis identified difficulties with follow-up and institutional constraints on scheduling and implementation of trials. Conclusions. CBT and mindfulness-based therapies are modestly effective in prisoners for depression and anxiety outcomes. In prisons with existing psychological therapies, more evidence is required before additional therapies can be recommended.